PENEGAKAN HUKUM PIDANA DALAM TINDAK PIDANA PENCABULAN TERHADAP ANAK (STUDI PUTUSAN NO. 396/PID.B/2012/PN-LP DI PENGADILAN NEGERI LUBUK PAKAM) - BOB SADIWIJAYA (USU LAW JOURNAL, 2013)
Law No.23/2002 on Child protection is expected to function as a safety valve for various criminal acts intended to children including criminal act of sexual abuse. But, this expectation is different from reality in which the criminal act of sexual abuse tends to increase from time to time. The legal provision on sexual abuse against children is regulated in the Indonesian Criminal Codes and law No.23/2002. The law enforcement in the case No. 396/Pid.B/2012/PN-LP was done accordance with the provision of the Indonesian Criminal Codes and law No.23/2002. Juridical constraint was the provision of Article 153 paragraph (3) of the Indonesian Criminal Codes and Article 64 paragraph (3) of Law No.23/2002 stating that decency court proceedings are closed to public and the absence of article regulating severe punishment for the adult perpetrators of child sexual abuse. The non-juridical constraints were the lack of human resources/court officials including the judges who are especially able to understand the problems of child psychology, the less representative facility and infrastructure such as the courthouse for the trials of the cases of decency and the cases which are closed to public. Keywords: Law Enforcement, Criminal Act, Sexual Abuse, Child